Modified hydrotalcite filler based on gallic acid and waterborne epoxy resin anticorrosive coating

By using gallic acid modified modified hydrotalcite filler in aqueous epoxy coating, the problems of poor density and poor long-term service effects of existing coatings are solved, and more efficient anti-corrosion effects of metal substrates are achieved and longer Service lifespan.

CN119432138APending Publication Date: 2025-02-14TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411772914.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing water-based epoxy coatings are difficult to effectively protect against corrosion behavior of metal substrates due to poor density and poor long-term service in marine environments.

Method used

A new type of aqueous epoxy coating was prepared by combining modified hydrotalcite filler based on gallic acid modification with aqueous epoxy resin. The modified hydrotalcite filler improves the corrosion resistance of the coating by combining the calcium-aluminum hydrotalcite carrier and gallic acid.

Benefits of technology

It significantly improves the anti-corrosion effect of the aqueous epoxy coating, extends the service life of the metal substrate, and shows excellent corrosion resistance and long-term service capabilities in marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432138A_ABST
    Figure CN119432138A_ABST
Patent Text Reader

Abstract

The invention discloses a modified hydrotalcite filler based on gallic acid and a water-borne epoxy resin anticorrosive coating, and belongs to the technical field of water-borne epoxy resin anticorrosive coatings. The preparation method comprises the following steps: selecting calcium-aluminum hydrotalcite as a precursor, loading a gallic acid corrosion inhibitor (GA) in the calcium-aluminum hydrotalcite through a reverse mixing acid-base precipitation method to obtain a modified hydrotalcite filler (LDH-GA), and adding the modified hydrotalcite filler into a waterborne epoxy coating to obtain a modified hydrotalcite anticorrosive coating (WEP / LDH-GA). In a 3.5% wt. NaCl solution, compared with a blank control WEP coating, the WEP / LDH-GA coating has relatively high corrosion resistance, and the corrosion current density is also reduced. The method is simple and convenient in steps and simple to operate, and the gallic acid loaded hydrotalcite improves the barrier corrosion resistance of the waterborne epoxy coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterborne epoxy resin anticorrosion coatings, and in particular to a gallic acid-based modified hydrotalcite filler and a waterborne epoxy resin anticorrosion coating, wherein the coating can be applied to the protection of metal substrate corrosion caused by chloride ions in a marine environment. Background Art

[0002] Metals serving in marine environments corrode due to the invasion of corrosive ions. For example, the actual service life of steel structures immersed in seawater is often lower than the ideal life. Water-based epoxy coatings have a certain covering effect and can cover the metal surface to delay corrosion.

[0003] In the prior art, environmentally friendly water-based epoxy resin coatings do not have excellent long-term barrier properties, which affects the service life of metals in marine environments. Therefore, it is necessary to increase the service life of epoxy coatings that can cover metals, which can not only protect metals but also reduce economic losses. Therefore, adding fillers with barrier / self-healing properties to water-based epoxy resins can significantly improve their anti-corrosion properties and effectively extend the life of metals, which has good application prospects. Summary of the invention

[0004] In view of the shortcomings of the prior art water-based epoxy coatings such as poor density and inability to achieve long-term service effects, the purpose of the present invention is to provide a modified hydrotalcite filler based on gallic acid and a water-based epoxy resin anti-corrosion coating. The prepared modified hydrotalcite filler modified with gallic acid can improve the anti-corrosion effect of the water-based epoxy resin anti-corrosion coating when used in the water-based epoxy resin anti-corrosion coating.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A gallic acid-based modified hydrotalcite filler is formed by taking calcium aluminum hydrotalcite as a carrier and loading gallic acid on the carrier.

[0007] Furthermore, the preparation process of the modified hydrotalcite filler (LDH-GA) comprises the following steps:

[0008] (1) using calcium aluminum hydrotalcite as a raw material to prepare a hydrotalcite dispersion (LDH dispersion), and transferring it to a three-necked flask for later use; using gallic acid as a raw material to prepare a gallic acid aqueous solution, and transferring it to a separating funnel for later use; dissolving sodium hydroxide in deionized water to obtain a sodium hydroxide solution;

[0009] (2) slowly adding the gallic acid aqueous solution in the separatory funnel of step (1) to the LDH dispersion under stirring, and after the addition is completed, mixing for 3-4 hours at a constant temperature of 70-90° C. and under magnetic stirring to obtain a milky white aqueous solution;

[0010] (3) After the milky white aqueous solution obtained in step (2) is placed at room temperature for 24-36 hours, the sodium hydroxide solution is slowly added dropwise to the milky white aqueous solution after the placement, and after the dropwise addition is completed, the solution is reacted under the stirring action of a magnetic stirrer until the pH value of the solution is greater than 10, thereby obtaining a dark green aqueous solution (containing the reaction product LDH-GA);

[0011] (4) using a centrifuge to remove unreacted substances in the dark green aqueous solution obtained in step (3), and washing with water to obtain a LDH-GA mud precipitate; the mud precipitate is dried to obtain the modified hydrotalcite filler (LDH-GA), which is then sealed and stored.

[0012] In the above step (1), the preparation process of the hydrotalcite dispersion (LDH dispersion) is: weighing calcium aluminum hydrotalcite (Ca-Al-LDH) in deionized water, dispersing it evenly under magnetic stirring conditions to obtain a hydrotalcite dispersion (LDH dispersion), and transferring the obtained hydrotalcite dispersion (LDH dispersion) to a three-necked flask for standby use; the hydrotalcite is calcium aluminum hydrotalcite (Ca-Al-LDH); the ratio of the calcium aluminum hydrotalcite to deionized water is (0.05-0.2) g: 100 ml; during the magnetic stirring process, the temperature is 45-60° C. and the stirring time is 30-60 minutes.

[0013] In the above step (1), the preparation process of the gallic acid aqueous solution is: weigh gallic acid solid, dissolve it in deionized water, and transfer it to a separatory funnel. The ratio of gallic acid to deionized water is (0.1-0.4) g: 100 ml.

[0014] In the above step (1), the concentration of the sodium hydroxide solution is 0.05-1 mol / / L.

[0015] In the above step (2), the stirring speed is 500-800 rpm;

[0016] In the above step (3), during the magnetic stirring process, the temperature is 40-70° C. and the stirring time is 30-60 minutes.

[0017] In the above step (4), the centrifuge speed is 8000-15000 r / min, the water washing times are 2-5 times, and the drying is carried out in an oven at 60-80° C. for 3-8 hours.

[0018] In the above step (1), the weight ratio of the hydrotalcite to gallic acid is (0.05-0.2):(0.3-0.6).

[0019] A water-based epoxy resin anti-corrosion coating is prepared using the modified hydrotalcite filler, which includes the modified hydrotalcite filler, a water-based epoxy resin and a curing agent; wherein: the weight of the modified hydrotalcite filler accounts for 0.05-3wt.% of the total weight of the coating, and the weight ratio of the water-based epoxy resin to the curing agent is (1-3):1.

[0020] The preparation process of the waterborne epoxy resin anti-corrosion coating is as follows: the waterborne epoxy resin and the modified hydrotalcite filler are mixed evenly in proportion, a curing agent is added, stirred evenly, and allowed to stand to expel bubbles; the obtained coating slurry is evenly coated on the surface of a steel substrate (such as Q235 steel) using a scraper bar, and is left at room temperature for more than 48 hours to allow the coating slurry to be completely cured, thereby obtaining the waterborne epoxy resin anti-corrosion coating (WEP / LDH-GA).

[0021] Before mixing the modified hydrotalcite filler with the waterborne epoxy resin, the modified hydrotalcite filler is first sieved with a 150-mesh screen, and then deionized water is added and added to the waterborne epoxy resin; the metal substrate is first polished to 2000 mesh with sandpaper step by step before coating. The ratio of the modified hydrotalcite filler to deionized water is (0.015-0.035) g: 0.1 ml.

[0022] The advantages and beneficial effects of the present invention are as follows:

[0023] 1. The gallic acid-modified hydrotalcite filler (LDH-GA) provided by the present invention is prepared at a controllable temperature at room temperature, has a simple operation process, and has a low price for the synthetic precursor.

[0024] 2. The present invention synthesizes gallic acid-modified hydrotalcite filler, and its gallic acid anion corrosion inhibitor can react with cations in the environment to form insoluble substances deposited on the metal surface when corrosion occurs, which actively protects the corroded area and achieves long-term service effect. In addition, the barrier effect of hydrotalcite itself can form synergistic protection with gallic acid corrosion inhibitor, so that the water-based epoxy coating demonstrates excellent anti-corrosion properties.

[0025] 3. In 3.5% wt. NaCl solution, compared with the blank control WEP coating, the WEP / LDH-GA coating of the present invention has higher corrosion resistance and the corrosion current density is also reduced.

[0026] 4. The preparation steps of the filler of the present invention are simple and easy to operate. The hydrotalcite filler loaded with gallic acid corrosion inhibitor improves the barrier and anti-corrosion performance of the waterborne epoxy coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Graphs showing the open circuit potential (OCP) of the coatings in Comparative Example 1, Example 1 and Example 2.

[0028] Figure 2 The Nyquist diagrams of the coatings in Comparative Example 1, Example 1 and Example 2; wherein (b) is a partial enlarged view of (a).

[0029] Figure 3 Bode diagrams of the coatings in Comparative Example 1, Example 1 and Example 2; wherein: (a) Bode-impedance modulus diagram; (b) Bode-phase angle diagram.

[0030] Figure 4 The potentiodynamic polarization curves (LSV) of the coatings in Comparative Example 1, Example 1 and Example 2 were immersed in a 3.5 wt. % NaCl solution for 1 hour.

[0031] Figure 5 Electrochemical impedance spectroscopy (EIS) test of the coating during immersion for 2 days in Comparative Example 1, Example 1 and Example 2; wherein: (a) Nyquist plot; (b) Bode-impedance modulus plot; (c) Bode-phase angle plot; (d) low-frequency impedance |Z| during immersion 0.01Hz Change comparison chart.

[0032] Figure 6 The macroscopic morphology of the coatings in Comparative Example 1, Example 1 and Example 2 after being immersed in a 3.5 wt. % NaCl solution for 2 days.

[0033] Figure 7 It is calcium aluminum hydrotalcite powder.

[0034] Figure 8 This is the LDH-GA filler prepared in Example 1. DETAILED DESCRIPTION

[0035] The following examples further illustrate the present invention. It should be understood that the present invention is not limited to the following embodiments, and the methods described in the experimental process are regarded as routine experimental methods unless otherwise specified. The materials described can be obtained from public commercial channels unless otherwise specified.

[0036] The invention provides a hydrotalcite filler modified by gallic acid and a waterborne epoxy resin anticorrosive coating. The preparation process of the modified hydrotalcite filler is as follows: gallic acid is added to a hydrotalcite dispersion, and the gallic acid-modified modified hydrotalcite filler is obtained by a back-mixing acid-base precipitation method.

[0037] Preferably, the amount of gallic acid added to the modified hydrotalcite filler during the preparation process is much greater than the amount of hydrotalcite added to ensure that the hydrotalcite is fully reacted.

[0038] The source of gallic acid ions in the modified hydrotalcite is gallic acid.

[0039] Preferably, each synthesis reaction time is 2 to 3 hours, and the magnetic stirring speed is in the range of 500 to 800 rpm.

[0040] The waterborne epoxy resin anticorrosive coating is composed of modified hydrotalcite filler, waterborne epoxy and curing agent, wherein the mass percentage of the filler is 0.5-3wt.%, and the weight ratio of the waterborne epoxy to the curing agent is preferably 1.5: 1. The curing agent used can be an epoxy curing agent such as polyamide 650 / 651.

[0041] The modified hydrotalcite filler, deionized water, water-based epoxy and curing agent are mixed and coated on the surface of the metal substrate, and cured into a film at room temperature to obtain a metal anti-corrosion coating.

[0042] The present invention comprehensively utilizes the complexing ability of gallic acid with cations in a corrosive environment and the barrier ability of hydrotalcite due to its own structural characteristics, and prepares the target filler through a hydrothermal method, thereby realizing a new type of barrier / self-repairing water-based epoxy coating - WEP / LDH-GA.

[0043] Comparative Example 1:

[0044] This example is the preparation of WEP coating, the process is as follows:

[0045] Mix 0.1 ml of deionized water, 1.5 g of water-based epoxy resin and 1 g of curing agent, stir for 5 minutes to mix them evenly, and then let them stand for 5 minutes to eliminate bubbles. Use a scraper to apply the resulting mixture to the surface of a polished and dried Q235 steel substrate, and let it stand for more than 48 hours at room temperature to obtain a WEP coating.

[0046] Embodiment 1:

[0047] This example is the preparation of WEP / LDH-GA coating (LDH-GA addition amount is about 0.2wt.%), and the process is as follows:

[0048] 1. Prepare calcium aluminum hydrotalcite (Ca-Al-LDH) raw material, which is in white powder state, such as Figure 7 Take 0.1g of calcium aluminum hydrotalcite (Ca-Al-LDH) in 100ml of deionized water, stir magnetically for 30 minutes at 50°C until it is evenly dispersed to obtain LDH dispersion, and transfer it to a three-necked flask for standby use;

[0049] 2. Take 0.3 g of gallic acid solid and add it to 100 ml of deionized water to obtain a gallic acid solution, and transfer it to a separatory funnel for later use;

[0050] 3. Take 0.4g of sodium hydroxide solid and dissolve it in 100ml of water to obtain a sodium hydroxide solution after the sodium hydroxide is completely dissolved. Set aside;

[0051] 4. Slowly add the gallic acid solution in the separatory funnel to the LDH dispersion under stirring. After the addition is completed, increase the temperature of the magnetic stirrer to 70°C and mix at 650 rpm for 3 hours to ensure sufficient mixing to obtain a milky white aqueous solution.

[0052] 5. After the milky white aqueous solution obtained in step 4 is placed at room temperature for 30 hours, the sodium hydroxide solution is slowly added dropwise to the milky white aqueous solution after the placement. After the addition is completed, the mixture is reacted for 30-60 minutes at 50° C. under the stirring action of a magnetic stirrer until the pH value of the solution is greater than 10, thereby obtaining a dark green aqueous solution (containing the reaction product LDH-GA);

[0053] 6. The dark green aqueous solution obtained in step 5 was centrifuged at 10000 r / min to remove unreacted substances, and washed with water three times to obtain a relatively pure LDH-GA mud precipitate; baked in an oven at 70° C. for 5 h to obtain a modified hydrotalcite filler (LDH-GA filler), such as Figure 8 Store sealed as shown.

[0054] 7. The modified hydrotalcite filler was first sieved with a 150-mesh sieve, and then 0.005 g of the sieved LDH-GA filler was added to 0.1 ml of deionized water, and then mixed with 1.5 g of waterborne epoxy resin and 1 g of curing agent and allowed to stand for 5 minutes (the amount of LDH-GA added in the slurry was about 0.2 wt.%). The resulting slurry was applied to the surface of the polished and dried Q235 steel substrate with a scraper, and allowed to stand for more than 48 hours at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / LDH-GA / coating).

[0055] Embodiment 2:

[0056] This example is the preparation of WEP / LDH-GA coating (LDH-GA addition amount is about 0.5wt.%), and the process is as follows:

[0057] 1. Take 0.1 g of the calcium aluminum hydrotalcite (Ca-Al-LDH) and dissolve it in 100 ml of deionized water. Stir it magnetically at 50°C for 30 minutes until it is evenly dispersed to obtain LDH dispersion. Transfer it to a three-necked flask for standby use.

[0058] 2. Take 0.3 g of gallic acid solid and add it to 100 ml of deionized water to obtain a gallic acid solution, and transfer it to a separatory funnel for later use;

[0059] 3. Take 0.4g of sodium hydroxide solid and dissolve it in 100ml of water to obtain a sodium hydroxide solution after the sodium hydroxide is completely dissolved. Set aside;

[0060] 4. Slowly add the gallic acid solution in the separatory funnel to the LDH dispersion under stirring. After the addition is completed, raise the temperature of the magnetic stirrer to 70°C and react for 3 hours under stirring at 700 rpm to allow the reaction to fully react and obtain a milky white aqueous solution.

[0061] 5. After the milky white aqueous solution obtained in step 4 is placed at room temperature for 30 hours, the sodium hydroxide solution is slowly added dropwise to the milky white aqueous solution after the placement. After the addition is completed, the reaction is carried out for 30-60 minutes under the stirring action of a magnetic stirrer at 50°C until the pH value of the solution is greater than 10, thereby obtaining a dark green aqueous solution (containing the reaction product LDH-GA).

[0062] 6. Use a centrifuge at 10,000 r / min to remove unreacted substances from the dark green aqueous solution obtained in step 5, wash with water three times to obtain a relatively pure LDH-GA mud precipitate; bake in an oven at 70° C. for 5 h to obtain a modified hydrotalcite filler (LDH-GA filler), and seal for storage.

[0063] 7. The modified hydrotalcite filler was first sieved with a 150-mesh sieve, and then 0.0125 g of the sieved LDH-GA filler was added to 0.1 ml of deionized water, and then mixed with 1.5 g of waterborne epoxy resin and 1 g of curing agent and allowed to stand for 5 minutes (the amount of LDH-GA added in the slurry was about 0.5 wt.%). The resulting slurry was applied to the surface of the polished and dried Q235 steel substrate with a scraper bar, and allowed to stand for more than 48 hours at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / LDH-GA / coating).

[0064] Figure 1 The open circuit potential diagrams of the WEP coating in comparative example 1, the WEP / LDH-GA coating with an addition amount of 0.2wt.% in Example 1, and the WEP / LDH-GA coating with an addition amount of 0.5wt.% in Example 2, which were immersed in a 3.5wt.% NaCl solution for 60 minutes, show that the potential of the WEP coating is stable at around -0.21V, the potential of the WEP / LDH-GA coating with an addition amount of 0.2wt.% is stable at around -0.16V, and the potential of the WEP / LDH-GA coating with an addition amount of 0.2wt.% is stable at around -0.10V. According to the fact that the more negative the potential moves, the greater the corrosion tendency, it can be seen that the coating with LDH-GA as filler reduces the corrosion resistance of WEP, while the WEP / LDH-GA coating with a filler addition amount of 0.5wt.% has better corrosion resistance and the lowest corrosion tendency.

[0065] Figure 2Nyquist plots of the coatings in comparative example 1 and examples 1-2; it can be seen that the impedance spectrum radius of the WEP coating in comparative example 1 is the smallest, while the impedance spectrum radius of examples 1-2 is significantly larger than that of the WEP coating; and by comparing the sizes of the arc radii in examples 1 and 2, it can be seen that the WEP / LDH-GA coating with an addition amount of 0.5wt.% has a larger arc radius, indicating that the coating in example 2 has the best corrosion resistance.

[0066] Figure 3 (a) is the Bode impedance modulus diagram, showing that at the lowest frequency, the impedance values ​​of the WEP coating, the WEP / LDH-GA coating with an addition amount of 0.2wt.%, and the WEP / LDH-GA coating with an addition amount of 0.5wt.% increase in sequence, and their impedance values ​​are 1.55×10 7 Ω.cm 2 4.85×10 8 Ω.cm 2 ,7.73×10 8 Ω.cm 2 , indicating that adding LDH-GA filler to waterborne epoxy will increase the corrosion resistance of the coating, and the corrosion resistance of the WEP / LDH-GA coating with an addition amount of 0.5wt.% is the most significant. Figure 5 (b) is the Bode phase angle diagram. According to the relative position in the diagram, the more it moves to the left, the better the corrosion resistance. It can be seen that the corrosion resistance of the WEP / LDH-GA coating with an addition amount of 0.5wt.% is the best.

[0067] Figure 4 The potentiodynamic polarization curves of the WEP coating in comparative example 1, the WEP / LDH-GA coating with an addition amount of 0.2wt.% in Example 1, and the WEP / LDH-GA coating with an addition amount of 0.5wt.% in Example 2 were immersed in a 3.5wt.% NaCl solution for one hour. Through fitting, it can be known that the corrosion current density of the WEP coating, the WEP / LDH-GA coating with an addition amount of 0.2wt.% and the WEP / LDH-GA coating with an addition amount of 0.5wt.% are respectively about 5.01×10 -8 A.cm -2 , 3.13×10 -9 A.cm -2 ,8.16×10 -10 A.cm -2 This once again proves that the hydrotalcite filler synthesized in the present invention can significantly enhance the corrosion resistance of the coating, and the coating's anti-corrosion performance becomes more excellent as the added amount increases.

[0068] Figure 5Electrochemical impedance spectroscopy (EIS) tests of the WEP coating in Comparative Example 1, the WEP / LDH-GA coating with an addition amount of 0.2 wt.% in Example 1, and the WEP / LDH-GA coating with an addition amount of 0.5 wt.% in Example 2 during immersion for 2 days; wherein, Figure 5 (a) Nyquist plot showing that the coating with LDH-GA filler has a larger arc radius; Figure 5 The Bode impedance modulus values ​​of (b) show that the impedance of the WEP coating at 12 h, d1, and d2 are 3.09×10 7 Ω.cm 2 , 1.18×10 7 Ω.cm 2 , 6.48×10 6 Ω.cm 2 The impedance of the WEP / LDH-GA coating with an addition amount of 0.2wt.% at the immersion time points of 12h, d1 and d2 were 6.24×10 7 Ω.cm 2 ,7.05×10 7 Ω.cm 2 , 5.98×10 7 Ω.cm 2 , while the impedance of the WEP / LDH-GA coating with an addition amount of 0.5wt.% at the immersion time points of 12h, d1 and d2 were 9.26×10 7 Ω.cm 2 ,7.13×10 7 Ω.cm 2 , 6.54×10 7 Ω.cm 2 ;Depend on Figure 5 (c) Bode-phase angle diagram shows that the phase angle position of the coating with LDH-GA filler is more to the left, proving that it has better corrosion resistance. Figure 5 (d) Low-frequency impedance during immersion |Z| 0.01Hz The change comparison diagram shows that the WEP coating, the WEP / LDH-GA coating with an addition amount of 0.2wt.% in Example 1, and the WEP / LDH-GA coating with an addition amount of 0.5wt.% in Example 2 gradually decrease with the increase of time, but the WEP / LDH-GA coating with an addition amount of 0.5wt.% in Example 2 has better durability, which is manifested in the low-frequency impedance |Z| 0.01Hz It was higher than other coatings at any time point.

[0069] Figure 6The macroscopic morphology of the coatings in Comparative Example 1, Example 1 and Example 2 after being immersed in 3.5wt.% NaCl solution for 2 days is shown. The WEP coating surface shows obvious metal peeling phenomenon, while the WEP / LDH-GA coating with an addition amount of 0.2wt.% in Example 1 and the WEP / LDH-GA coating with an addition amount of 0.5wt.% in Example 2 show pitting on the surface, and the pitting becomes milder with the increase of the addition amount.

[0070] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application. The above are only preferred implementations of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A modified hydrotalcite filler based on gallic acid, characterized in that: The modified hydrotalcite filler is formed by taking calcium aluminum hydrotalcite as a carrier and loading gallic acid on the carrier.

2. The modified hydrotalcite filler based on gallic acid according to claim 1, characterized in that: The preparation process of the modified hydrotalcite filler (LDH-GA) comprises the following steps: (1) using calcium aluminum hydrotalcite as a raw material to prepare a hydrotalcite dispersion (LDH dispersion), and transferring it to a three-necked flask for standby use; using gallic acid as a raw material to prepare a gallic acid aqueous solution, and transferring it to a separatory funnel for standby use; dissolving sodium hydroxide in deionized water to obtain a sodium hydroxide solution; (2) slowly adding the gallic acid aqueous solution in the separatory funnel of step (1) to the LDH dispersion under stirring, and after the addition is completed, mixing for 3-4 hours at a constant temperature of 70-90° C. and under magnetic stirring to obtain a milky white aqueous solution; (3) After the milky white aqueous solution obtained in step (2) is placed at room temperature for 24-36 hours, the sodium hydroxide solution is slowly added dropwise to the milky white aqueous solution after the placement, and after the dropwise addition is completed, the solution is reacted under the stirring action of a magnetic stirrer until the pH value of the solution is greater than 10, thereby obtaining a dark green aqueous solution (containing the reaction product LDH-GA); (4) using a centrifuge to remove unreacted substances in the dark green aqueous solution obtained in step (3), and washing with water to obtain a LDH-GA mud precipitate; after drying the mud precipitate, the gallic acid-based modified hydrotalcite filler (LDH-GA) is obtained, which is sealed and stored.

3. The modified hydrotalcite filler based on gallic acid according to claim 2, characterized in that: In step (1), the preparation process of the hydrotalcite dispersion (LDH dispersion) is as follows: calcium aluminum hydrotalcite (Ca-Al-LDH) is weighed in deionized water, and the mixture is evenly dispersed under magnetic stirring to obtain a hydrotalcite dispersion (LDH dispersion), and the obtained hydrotalcite dispersion (LDH dispersion) is transferred to a three-necked flask for standby use; the ratio of the calcium aluminum hydrotalcite to deionized water is (0.05-0.2) g: 100 ml; during the magnetic stirring process, the temperature is 45-60° C. and the stirring time is 30-60 minutes.

4. The gallic acid-modified hydrotalcite filler according to claim 2, characterized in that: In step (1), the preparation process of the gallic acid aqueous solution is: weigh gallic acid solid, dissolve it in deionized water, and transfer it to a separatory funnel; wherein: the ratio of gallic acid to deionized water is (0.1-0.4) g: 100 ml; the concentration of the sodium hydroxide solution used to adjust the pH value is 0.05-1 mol / / L.

5. The modified hydrotalcite filler based on gallic acid according to claim 2, characterized in that: In step (2), the stirring speed is 500-800 rpm; in step (3), during the magnetic stirring process, the temperature is 40-70°C and the stirring time is 30-60 minutes; in step (4), the centrifuge speed is 8000-15000 r / min, the number of water washings is 2-5 times, and the drying is performed by baking in an oven at 60-80°C for 3-8 hours.

6. The gallic acid-modified hydrotalcite filler according to claim 2, characterized in that: In step (1), the weight ratio of calcium aluminum hydrotalcite to gallic acid is (0.05-0.2): (0.3-0.6).

7. A water-based epoxy resin anticorrosive coating prepared using the modified hydrotalcite filler according to claim 1, characterized in that: The waterborne epoxy resin anticorrosive coating comprises the modified hydrotalcite filler, waterborne epoxy resin and curing agent; wherein: the modified hydrotalcite filler accounts for 0.05-3wt.% of the weight of the coating, and the weight ratio of the waterborne epoxy resin and the curing agent in the coating is (1-3):

1.

8. The waterborne epoxy resin anticorrosive coating according to claim 7, characterized in that: The preparation process of the waterborne epoxy resin anti-corrosion coating is as follows: the waterborne epoxy resin and the modified hydrotalcite filler are mixed evenly in proportion, a curing agent is added, stirred evenly, and allowed to stand to expel bubbles to obtain a coating slurry; the obtained coating slurry is evenly coated on the surface of a steel substrate using a scraper bar, and is left at room temperature for more than 48 hours to completely cure the coating slurry, thereby obtaining the waterborne epoxy resin anti-corrosion coating (WEP / LDH-W-Ce).

9. The waterborne epoxy resin anticorrosive coating according to claim 8, characterized in that: Before the modified hydrotalcite filler is mixed with the waterborne epoxy resin, the modified hydrotalcite filler is first sieved with a 150-mesh screen, and then deionized water is added, and then added to the waterborne epoxy resin; the metal substrate is first polished to 2000 mesh using sandpaper step by step before coating; the ratio of the modified hydrotalcite filler to deionized water is (0.015-0.035) g: 0.1 ml.

Citation Information

Patent Citations

  • Preparation method of anti-corrosion and anti-erosion multifunctional coating

    CN116213227A

  • Gallic acid intercalated zinc-aluminum hydrotalcite anticorrosive filler as well as preparation method and application thereof

    CN116770298A

  • Corrosion-resistant modified hydrotalcite, multifunctional coating and preparation methods of corrosion-resistant modified hydrotalcite and multifunctional coating

    CN117089232A